Asymptomatic cytomegalovirus gastritis in an immunocompetent COVID-19 patient: a case report - Fizza Najeeb; Maria Iqbal; Syed Mohammad Mehmood Abbas; Tahir Iqbal (Journal of the Pakistan Medical Association)
A number of complications are associated with COVID-19 due to reduced immunity. Of these, opportunistic infections are of great significance because of their atypical presentation and low detection rates. Co-infection of various parts of the gastrointestinal system with cytomegalovirus (CMV) is a common occurrence in COVID-19 patients. Dysphagia and odynophagia are the main complaints of oesophagitis caused by CMV. Colitis due to CMV presents with melena, diarrhoea, or constipation. However, gastritis due to the same agent can be asymptomatic or associated with atypical symptoms like fever and epigastric pain. Cytomegalovirus gastritis can be fatal if not detected early. Hence, continued monitoring of routine baseline investigations is imperative until the complete resolution of COVID-19, as prompt diagnosis improves the outcomes.